Mechanical and Fatigue Properties of Gravity Die-Cast A356 Aluminium Alloy with Addition of Scandium - A, Masita; Yeo, W.H.; Saw, L.H.; Lim, Y.P; Lee, J.W; Ng, T.C. (IOP Publishing, 2019)
A356 is widely used for the casting of high strength components in automotive, aerospace and other industrial applications. This is due to its high achievable strength, castability, light weight, good thermal and electrical conductivity. However, the as-cast A356 exhibits relative poor mechanical properties due to the presence of coarse acicular eutectic silicon morphology. In this study, Sc-modified-A356 and the effect of heat treatment have been studied and compared with unmodified A356. Various amounts of Sc ranging from 0.2 wt% to 0.6 wt% were added into the mixture of A356 aluminium alloy and the specimens were produced by using gravity die-casting. Next, the ultimate tensile strength, Vickers hardness and fatigue behaviour of the cast samples are examined. The results revealed that by adding 0.4 wt.% of Sc, the heat treated sample is able to achieve ultimate tensile strength of above 300 MPa and Vicker’s hardness of 118 HV. Furthermore, the fatigue properties of the 0.4 wt% Sc-A356 with T6 heat treatment was found to be improved as compared to the unmodified A365 samples.